Promoting Critical Literacy in Academic Reading Class: EFL Learners’ Activity Exploration - Hendi Hidayat; Issy Yuliasri; Dwi Rukmini; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2022)
Abstrak. The goal of this study was to investigate what EFL students did in academic reading class. The goal of the lesson is to prepare students to respond intelligently and critically to academic texts and to issues raised in written assignments. The idea behind this reading reaction has been influenced by Rosenblatt's research. She considers the act of reading to be a live event. The author believes that it would be useful to adapt this concept to academic reading even if it was often employed by literary majors. Qualitative information is provided to show how these pupils engage with text critically. In order to gather data for this study, the author observed, spoke with, and examined the written work of learners. The paper's recommendations for teachers to develop their own critical literacy approach to texts and modules are provided in the last section. In order to finish their output, the EFL students in this study employed a careful selection of texts, background knowledge activation, questions about the author's ideas, intertextuality for responding to the questions, and reflection.